Risk factors associated with the transmissionof Brazilian spotted fever in the Piracicaba river basin, State of São Paulo, Brazil - Souza,Celso Eduardo de (2015)
INTRODUCTION : Brazilian spotted fever (BSF) is a disease transmitted by ticks for which the etiological agent is Rickettsia rickettsii. The present essay evaluates the risk factors associated with the transmission of cases of BSF in the time period between 2003 and 2013 in the Piracicaba river basin, state of São Paulo. METHODS : This essay presents a retrospective study to identify the factors associated with the transmission of cases of BSF among all suspected cases identified by the System for Epidemiological Surveillance of São Paulo (CVE). After the description of temporal distribution (onset of symptoms) and the environmental and demographic variations of the confirmed and discarded cases, a multiple logistic regression model was applied. RESULTS : We searched 569 probable locations of infection (PLI) with 210 (37%) confirmed cases of BSF and 359 (63%) discarded cases. The associated variables for the confirmation of BSF in the multiple logistic model using a confidence interval (CI) of 95% were age (OR = 1.025 CI: 1.015-1.035), the presence of Amblyomma sculptum in the environment (OR = 1.629 CI: 1.097-2.439), the collection of ticks from horses (OR = 1.939 CI: 0.999-3.764), the presence of capybaras (OR = 1.467 CI: 1.009-2.138), an urban environment (OR = 1.515 CI: 1.036-2.231), and the existence of a dirty pasture (OR = 1.759 CI: 1.028-3.003). CONCLUSIONS : The factors associated with the confirmation of BSF cases included an urban environment, age, presence of the A. sculptum vector, the collection of ticks from horses, the presence of a capybara population, and a dirty pasture environment.